(untitled) (Jurnal Arsitektur ARCADE, 2026)
The building sector is a major global energy consumer, with windows being the most critical element for heat gain in tropical climates. This research aims to investigate the optimal Window-to-Wall Ratio (WWR) and glass material selection for energy efficiency in hotel building, using Hotel Voyou in Surakarta as a case study. The methodology employs a qualitative approach through descriptive analysis and expert validation (Expert Validation) involving three key stakeholders: a practitioner architect, a green building expert from GBCI, and a glass material vendor. The results confirm that a WWR range of 20-60% is the optimal efficiency zone for balancing daylighting and cooling loads. Among the tested materials, Sunergy Blue Green (Low-E) is the most recommended choice due to its low U-Value (4.1 W/m2K) and Shading Coefficient (0.43), which effectively reduces heat gain without compromising visual quality. The study concludes that WWR and material performance are interdependent; higher WWR can still achieve energy efficiency if paired with high-performance glazing.